Study of etiology of pleural effusion in Telangana population - Mohiuddin, Mohd Ifthekhar; Patel, Parth N. (International Journal of Advances in Medicine, 2019)
Background: Among 86 patients aged between 18 to 65 of both sexes having pleural effusion due to various clinical etiologies were studied. Methods: Chest x-ray PA. was studied, 20 ml of pleural fluid was aspirated to study bio-chemically, microbiologically and pathological. Echo-cardiography, USG abdomen and biopsy of pleura was also done in same patients in whom diagnosis or etiology was unclear. Results: Among 59(68.6%) had fever, 68(79%) had cough, 40(46.5%) had breathlessness, 20(23.2%) had pedal edema, 42(48.8%) had chest pain, 5(5.8%) had abdominal distention. 52(60.4%) had tubercular pleural effusion 34(39.5%) had non- tubercular pleural types of non-tubercular PE effusion (PE) included 8(23.5%) synpneumonic, 5(14.7%) had CCF, 11(32.3%) had malignancy, 2(5.88%) had RA, 2(5.88%) had dengue fever, 2(5.88%) had pancreatitis, 4(11.7%) had Hypoproteinaemia. Conclusions: This pragmatic approach to pleural effusion for patients with different clinical manifestations as pleural fluid analysis is gold standard method in evaluation pleural effusion of different etiology. Background: Among 86 patients aged between 18 to 65 of both sexes having pleural effusion due to various clinical etiologies were studied. Methods: Chest x-ray PA. was studied, 20 ml of pleural fluid was aspirated to study bio-chemically, microbiologically and pathological. Echo-cardiography, USG abdomen and biopsy of pleura was also done in same patients in whom diagnosis or etiology was unclear. Results: Among 59(68.6%) had fever, 68(79%) had cough, 40(46.5%) had breathlessness, 20(23.2%) had pedal edema, 42(48.8%) had chest pain, 5(5.8%) had abdominal distention. 52(60.4%) had tubercular pleural effusion 34(39.5%) had non- tubercular pleural types of non-tubercular PE effusion (PE) included 8(23.5%) synpneumonic, 5(14.7%) had CCF, 11(32.3%) had malignancy, 2(5.88%) had RA, 2(5.88%) had dengue fever, 2(5.88%) had pancreatitis, 4(11.7%) had Hypoproteinaemia. Conclusions: This pragmatic approach to pleural effusion for patients with different clinical manifestations as pleural fluid analysis is gold standard method in evaluation pleural effusion of different etiology.